Menjelajahi Nirwana Akademik Analisis Keberhasilan Universitas Muhammadiyah Jawa Timur dalam Memenangkan Hati Mahasiswa Melalui Kompetensi Staff Akademik, Keandalan Layanan dan Kilau Reputasi - Intan Sari, Rosi Avinda; Cahyono, Dwi; Susbiyani, Arik (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to analyze the influence of the variables of Academic Staff Competence, Service Reliability, and University Reputation on Student Satisfaction in Muhammadiyah Universities in East Java using hypothesis testing method with the assistance of SPSS (Statistical Package for the Social Sciences) software. Data collected from 240 student respondents were analyzed to test the impact of these variables on student satisfaction. The SPSS analysis results show that all three variables, namely Academic Staff Competence, Service Reliability, and University Reputation, both simultaneously and partially, have a significant positive influence on student satisfaction. These findings have significant implications for higher education institutions, especially in designing strategies to improve service quality, develop academic staff competence, and enhance university reputation collectively. Keywords: Academic Staff Competence, Muhammadiyah Universities in East Java, University Reputation, Student Satisfaction, Service Reliability.